2024
DOI: 10.3390/plants13020274
|View full text |Cite
|
Sign up to set email alerts
|

RNA-Seq-Based WGCNA and Association Analysis Reveal the Key Regulatory Module and Genes Responding to Salt Stress in Wheat Roots

Jiating Chen,
Lei Zhang,
Yingxi Liu
et al.

Abstract: Soil salinization is the main abiotic stressor faced by crops. An improved understanding of the transcriptional response to salt stress in roots, the organ directly exposed to a high salinity environment, can inform breeding strategies to enhance tolerance and increase crop yield. Here, RNA-sequencing was performed on the roots of salt-tolerant wheat breeding line CH7034 at 0, 1, 6, 24, and 48 h after NaCl treatment. Based on transcriptome data, a weighted gene co-expression network analysis (WGCNA) was constr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…Studies have shown that melatonin can stimulate the synthesis of GSH [58]. In this study, 18 and 41 differentially expressed genes were enriched in the glutathione pathway in the NaCl and MT treatment groups, among which 16 and 27 genes were related to GST, respectively, which have been proven to play a key role in combating salt stress [59][60][61]. In the melatonin-treated group, genes related to GST were significantly upregulated, which may be because melatonin promotes the expression of GST, thereby catalyzing GSH to neutralize reactive oxygen species.…”
Section: The Roles and Connections Between Physiological Indicatorsmentioning
confidence: 62%
“…Studies have shown that melatonin can stimulate the synthesis of GSH [58]. In this study, 18 and 41 differentially expressed genes were enriched in the glutathione pathway in the NaCl and MT treatment groups, among which 16 and 27 genes were related to GST, respectively, which have been proven to play a key role in combating salt stress [59][60][61]. In the melatonin-treated group, genes related to GST were significantly upregulated, which may be because melatonin promotes the expression of GST, thereby catalyzing GSH to neutralize reactive oxygen species.…”
Section: The Roles and Connections Between Physiological Indicatorsmentioning
confidence: 62%
“…A set of wheat germplasm comprising 97 hexaploid accessions (Triticum aestivum L.) [38], including 38 landraces and 59 modern cultivars (Table S1), was used to estimate the adaptability and the allele distribution of QTL. All the plant materials were planted in the greenhouse at Shanxi Agricultural University (Taiyuan, China) in 2022.…”
Section: Plant Materialsmentioning
confidence: 99%